IDENTIFIKASI FAKTOR – FAKTOR PENYEBAB PERILAKU PEDOFILIA PADA NARAPIDANA DI LAPAS KLAS I CIPINANG JAKARTA - Arrum Aulirachmah; Kusyogo Cahyo; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2017)
In 2016, 42% of all children’s HIV cases of Indonesia happen in Jakarta. Besides catching HIV from their mothers, children can get infected if they become victims of sexual abuse. Sexual abuse can causes HIV because the perpetrators usually done the act with many victims.Sexual abuse experience also gives negative effects on child’s psychological and social development. As high as 33,7% of all sexual abuse cases towards children of Indonesia happen in Jakarta. The tendency to have sexual intercourse with children is called Pedophilia. Most of the pedophiles that were caught in Jakarta have been sentenced in Lapas Klas I Cipinang, which is the biggest in the city.This research aims to identify the factors that support the behaviour of the pedophile prisoners of Lapas cipinang. This research uses the qualitative method. This research uses 6 prisoners as main informan and 3 triangulation informans. Datas collected with indepth interview and processed with content analysis. The results of this research shows  that the factors of pedophilic behaviour of prisoners of Lapas cipinang are the evaluation that this behavior gives advantages, positive attitude and normative belief toward the behaviour, motivations and positive subjective norm in the act, and the intentions before the act. As shown above, providing private phsycologs for Pedophilic prisoners is suggested for Lapas Klas I Cipinang Jakarta.  Giving communication, information, and education about early sexual education is suggested for Ministry of Women and Child Protection, schools, and parents to avoid addition of Pedophilia victim in Indonesia, especially Jakarta.